Ekbom syndrome, an evidence based review of literature - Lutfi, Ahmed M (Asian Journal of Medical Sciences, 2016)
Delusional Parasitosis (DP) is a Psychocutaneous disorder that was 1st described in the late 17th century in France. The etiology is neuro-chemical. The classic “matchbox” and “specimen” signs are characteristic. Management is via a multidisciplinary approach. This review paper is based on detailed systematic review of literature via an up-to-date evidence based approach. This paper reviews: Historical facts, epidemiology, pathogenesis, clinical features, subtypes, associated diseases, psychosocial impact, economic considerations and management. An exhaustive search strategy was utilized across five medical literature databases led by 62 pre-specified keywords, followed by database-specific filters’ application to scrutinize the hierarchy of literature, from systematic reviews and randomized controlled trials to medical papers with weak evidence. Forty references were utilized to extract the most relevant data. This review article is level II-3 (level of evidence); it will enable the researcher to obtain a perspective of DP, upon which an original research can be developed. Asian Journal of Medical Sciences Vol. 7(3) 2016 1-8